2021
DOI: 10.5194/nhess-21-2733-2021
|View full text |Cite
|
Sign up to set email alerts
|

Modelling earthquake rates and associated uncertainties in the Marmara Region, Turkey

Abstract: Abstract. Modelling the seismic potential of active faults and the associated epistemic uncertainty is a fundamental step of probabilistic seismic hazard assessment (PSHA). We use SHERIFS (Seismic Hazard and Earthquake Rate In Fault Systems), an open-source code allowing us to build hazard models including earthquake ruptures involving several faults, to model the seismicity rates on the North Anatolian Fault (NAF) system in the Marmara Region. Through an iterative approach, SHERIFS converts the slip rate on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The inter-event time for these magnitudes is around 2000 -6000 years (Figure 4). From a probabilistic point of view, these models have shown in the Probabilistic Seismic Hazard Analyses (PSHA) a great potential to estimate recurrence periods and inter-event times for large earthquakes, which are poorly represented in the instrumental seismic catalogues (Chartier et al, 2021;Herrero-Barbero et al, 2021;Console et al, 2017); being one of the key pieces in the current development of seismic forecast models (Dieterich and Richards-Dinger, 2010;Field, 2019;Field et al, 2014;Shaw et al, 2018). The implementation of these methodologies in the Probabilistic Tsunami Hazard Analyses (PTHA) is a logical and necessary step.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inter-event time for these magnitudes is around 2000 -6000 years (Figure 4). From a probabilistic point of view, these models have shown in the Probabilistic Seismic Hazard Analyses (PSHA) a great potential to estimate recurrence periods and inter-event times for large earthquakes, which are poorly represented in the instrumental seismic catalogues (Chartier et al, 2021;Herrero-Barbero et al, 2021;Console et al, 2017); being one of the key pieces in the current development of seismic forecast models (Dieterich and Richards-Dinger, 2010;Field, 2019;Field et al, 2014;Shaw et al, 2018). The implementation of these methodologies in the Probabilistic Tsunami Hazard Analyses (PTHA) is a logical and necessary step.…”
Section: Discussionmentioning
confidence: 99%
“…The result is a long synthetic earthquake catalogue including a comprehensive and detailed record of complex earthquake ruptures with heterogeneous slip. Recent results obtained using the RSQSim code are promising in relation to potential practical applicability (Chartier et al, 2021;Herrero-Barbero et al, 2021;Howarth et al, 2021;Shaw et al, 2018).…”
Section: Earthquake Ruptures Simulationmentioning
confidence: 97%
“…Many research has been done about earthquakes such as [20][21][22][23]. Also, research that focuses on solving uncertainty problems had been discussed [24][25][26][27] and research that involves spline function as spline interpolation can be referred to by [28].…”
Section: Fuzzy Interpolation Curve Modellingmentioning
confidence: 99%
“…(2021) employed RSQSim to establish a nonergodic framework for probabilistic seismic‐hazard analysis, while Chartier et al. (2021) utilized RSQSim as an auxiliary tool for weighting a logic tree that explores seismicity uncertainties in the Sea of Marmara. These papers demonstrate the utility of RSQSim and coupled with its increasing availability suggest that it will continue to have seismic hazard applications.…”
Section: Introductionmentioning
confidence: 99%
“…Shaw et al (2018) found that RSQSim simulations for the Californian fault system can replicate the seismic hazard statistics from the long-term Third Uniform California Earthquake Rupture Forecast (UCERF3; Field et al, 2014). Similarly, Milner et al (2021) employed RSQSim to establish a nonergodic framework for probabilistic seismic-hazard analysis, while Chartier et al (2021) utilized RSQSim as an auxiliary tool for weighting a logic tree that explores seismicity uncertainties in the Sea of Marmara. These papers demonstrate the utility of RSQSim and coupled with its increasing availability suggest that it will continue to have seismic hazard applications.…”
mentioning
confidence: 99%